Single-blind, randomized, controlled trial of pelvic floor muscle training, electrical stimulation, vaginal cones, and no active treatment in the management of stress urinary incontinence - Castro, Rodrigo A. (2008)
PURPOSE: To compare the effectiveness of pelvic floor exercises, electrical stimulation, vaginal cones, and no active treatment in women with urodynamic stress urinary incontinence. PATIENTS AND METHODS: One hundred eighteen subjects were randomly selected to recieve pelvic floor exercises (n=31), ES (n=30), vaginal cones (n=27), or no treatment (untreated control) (n=30). Women were evaluated before and after completion of six months of treatment by the pad test, quality of life questionnaire (I-QOL), urodynamic test, voiding diary, and subjective response. RESULTS: In the objective evaluation, we observed a statistically significant reduction in the pad test (p=0.003), in the number of stress urinary episodes (p